Top-Down Control of Inhibitory Granule Cells in the Main Olfactory Bulb Reshapes Neural Dynamics Giving Rise to a Diversity of Computations - Chen, Zhen; Padmanabhan, Krishnan (Frontiers in Computational Neuroscience, 2020)
Growing evidence shows that top-down projections from excitatory neurons in piriform cortex selectively synapse onto local inhibitory granule cells in the main olfactory bulb, effectively gating their own inputs by controlling inhibition. An open question in olfaction is the role this feedback plays in shaping the dynamics of local circuits, and the resultant computational benefits it provides. Using rate models of neuronal firing in a network consisting of excitatory mitral and tufted cells, inhibitory granule cells and top-down piriform cortical neurons, we found that changes in the weight of feedback to inhibitory neurons generated diverse network dynamics and complex transitions between these dynamics. Changes in the weight of top-down feedback supported a number of computations, including both pattern separation and oscillatory synchrony. Additionally, the network could generate gamma oscillations though a mechanism we termed Top-down control of Inhibitory Neuron Gamma (TING). Collectively, these functions arose from a codimension-2 bifurcation in the dynamical system. Our results highlight a key role for this top-down feedback, gating inhibition to facilitate often diametrically different computations.